Naturally Induced Hazards in the Agra Khola Warershed, Central Hills, Nepal - Sharma, Puspa (Himalayan Review, 2011)
Available with fulltext. Key words: GIS; Landslide; Natural hazards; Geology elevation The Himalayan Review Nepal Geographical Society Vol. XXXI 2000 Page: 81-94 Uploaded date: 5 June, 2011